The Cord Keepers : Khipus and Cultural Life in a Peruvian Village - Salomon, Frank (Book collections on Project MUSE., 2004)
An ethnography of Andean knot writing, where media convey information without an alphabet or any other visual likeness of speech, examining the ways that such "mute inscription" communicates social experience.